Effectiveness of attachment-based compassion therapy to reduce psychological distress in university students: a randomised controlled trial protocol - Beltrán-Ruiz, María; Fernández, Selene; García-Campayo, Javier; Puebla-Guedea, Marta; López-del-Hoyo, Yolanda; Navarro-Gil, Mayte; Montero-Marin, Jesus (Frontiers in Psychology, 2023)
Introduction: Higher education, particularly university, is a challenge for many students that can lead to their mental health being seriously affected. The stress to which they are subject throughout their time at university can lead to anxiety and depression. 'Third wave' psychotherapies, including compassion-based therapy, have been used to improve psychological outcomes, such as stress, anxiety, emotional distress and well-being. There are some signs that third wave psychotherapies reduce psychological distress in university students, but more and higher-quality studies are needed. In this randomised controlled trial (RCT), we hypothesise that the provision of attachment-based compassion therapy (ABCT) will be more effective than an active control group based on relaxation therapy for improving psychological distress in university students.A two-arm RCT will be conducted involving 140 university undergraduate and postgraduate students from the University of Zaragoza and the National University of Distance Education (UNED) who reside in the autonomous community of Aragon, Spain. Interventions with either ABCT or relaxation therapy will be implemented, with an allocation ratio of 1:1 between groups. Both interventions will last six weeks and consist of six weekly group sessions lasting 1.5 hours each. Data will be collected before and after the intervention, and there will be a follow-up at six months. The primary outcome will be psychological distress at post-intervention. Secondary outcomes will be depression, anxiety, stress and burnout symptoms, affectivity and emotional regulation. Attachment style, experiential avoidance, compassion (for others/oneself) and mindfulness skills will be measured as potential mechanistic variables. Intention-to-treat analysis will be performed using linear mixed regression models. The clinical significance of improvements will be calculated.Potential side effects will be monitored by an independent clinical psychologist.Committee of Aragón. Participant data will remain anonymous, and results will be submitted to peer-reviewed open-access journals and disseminated via conferences.Trial registration number: ClinicalTrials.gov NCT05197595.